Ecological factors affecting growth and ochratoxin A production of Aspergillus section Nigri species on grapes - Mitchell, D. (Cranfield University, 2006)
This study investigated the effects of interacting environmental factors on the ecophysiology of Aspergillus carbonarius and ochratoxin A (OTA) production, to facilitate the building of a database of knowledge for risk prevention. Spore germination and germ tube extension was faster on grape flesh than in vitro on grape- based media, or grape skin. Under optimum conditions (25-35°C; 0.90-0.99 water activity (aw)) 50% of conidia germinated in < 4.5 hours. Two dimensional profiles in relation to aw x temperature were constructed for rate of germination and germ tube extension for the first time. Mycelial growth was also influenced by aw, temperature, pH and modified atmospheres. Two dimensional temporal profiles of growth and OTA production were constructed based on information on strains from four different European countries. This showed that the optimum aw and temperature, and range were 0.98 aw, 30°C and 0.99-0.88 aw and 15-40°C, respectively. In contrast, for OTA production these were 0.95 aw, 15-20°C, and 0.99-0.93 aw and 15-35°C respectively. Environmental factors also influenced mycelial interactions between A. carbonarius and nine other common grape fungi. An Index of Dominance showed that A. carbonarius was very competitive against these species over a range of aw levels and temperatures. OTA production was generally suppressed by interactions at 0.95 aw with some inhibition of OTA production at 30°C at 0.99 and 0.95 aw. At 0.99 and 20°C all strains except two species produced a stimulation in OTA production. The efficacy of fungicides (5) and anti-oxidants (2) on growth and OTA production was limited at the concentration used. The only two fungicides that did suppress growth were Switch (cyprodinil and fludioxonil) and carbendazim. OTA production was stimulated at sub-optimal concentrations regardless of aw level used. Anti-oxidants were ineffective under all conditions tested. Modified atmospheres (0.03, 25 and 50% CO2) at different aw levels showed that there was very little long term effect on spore germination and germ tube extension, even at 50% CO2. Regardless of aW) OTA production was influenced more by the aw itself than CO2 concentrations. The efficacy of Sodium metabisulphite (NaMBS) at different aw levels (0.99, 0.97, 0.93 aw) on grape juice-based media at 25°C on germination and germ tube extension showed inhibition by >500 mg kg' 1 of NaMBS. Low concentrations (100, 250 mg kg'1) stimulated growth and OTA production. LD50 and LD90 ranges were determined for both growth and OTA production for the first time. Field sampling found that black aspergill! were present on grapes from setting to harvest with a significant increase in the population with grape ripening, and higher temperatures. The most commonly isolated OTA species from grapes was A. carbonarius with no Pénicillium verrucosum and only a few Aspergillus ochraceus isolated. In all the field sampling found no OTA present in any of the grape musts.